PENGARUH PERSEPSI MAHASISWA TERKAIT PEMBELAJARAN DARING VIA LENTERA TERHADAP MOTIVASI BELAJAR MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA: THE INFLUENCE OF STUDENTS' PERCEPTIONS RELATED TO ONLINE LEARNING VIA LENTERA ON STUDENT'S LEARNING MOTIVATION IN THE MATHEMATICS EDUCATION DEPARTMENT - Rara Aprilyanti; Andi Ika Prasasti Abrar; Suharti (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to determine the description of students' perceptions regarding online learning via lentera, as well as the learning motivation of students majoring in mathematics education, and to find out whether there is an effect of student perceptions regarding online learning via lentera on students' learning motivation majoring in mathematics education. This type of research is ex-post facto. The population in this study were students of the Mathematics Education Department of UIN Alauddin Makassar class 2018, 2019, and 2020 with a total of 251 students and a sample of 154 students. The instruments used in this research are questionnaires and documentation. The analytical technique used is descriptive statistical analysis and inferential statistical analysis with hypothesis testing using a simple linear regression formula. The results of the study indicate that there is an influence of student perceptions regarding online learning via lentera on the learning motivation of students majoring in mathematics education. Based on the results of data analysis using descriptive statistics for student perceptions related to online learning via lantern (X), the average score of 54.02 is in the medium category, while for the learning motivation of students majoring in mathematics education (Y) an average value of 48.47 is obtained are in the medium category.